The transformation of teaching practice through the use of digital tools in higher middle education (Research, Society and Development, 2023)
The future of education is changing, so teacher training is necessary to ensure the use and use of available digital tools. The objective of this research is to know and analyze how digital tools have transformed teaching practice at the upper secondary level through the use of ICT/TAC/TEP by teachers. A methodological design of this exploratory-descriptive and transactional research was used since it has a theoretical section that supports the base constructs of this research, this part was carried out through a review of the literature in reliable sites, scientific articles and verified sites to have theoretical bases in the integration of TIC/TAC/TEP with the technological development, communicative pedagogy, administration and investigation. As well as counting new ways of carrying out learning in upper secondary education in a different way, counting teaching practices based on technology in a flexible way with a technological articulation oriented towards educational innovation.